SCREENING AND TRADING PROCEDURES IN THE SHARIA CAPITAL MARKET - Ihsan Helmi Lubis (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2023)
Sharia capital market is an activity concerned with public offerings and trading of securities, public companies related to securities issued, as well as institutions and professions related to securities that are run on the basis of sharia principles. This is certainly not separated from the screening procedures that must be passed to get into the Jakarta Islamic Indexs (JII). This means not all types of shares can enter in JII. The purpose of this screening is to fulfill the principle that an investor only transactions (trading) on something kosher or not contrary to Islamic Sharia. This paper will try to expose the screening procedure until trading in the sharia capital market.